Templos de civilização no Pará: a institucionalização dos grupos escolares (1890-1910) - Lobato, Ana Maria Leite (2014)
This thesis has the purpose of institutionalization of School Groups in the State of Pará from 1890 to 1910, and republicanism as plot and the school model. The study has its basis in cultural history and had the approach of Micro-history of Ginzburg (1987) and Sword (2006). Within the study of the history of education has been questioned in relation to modern school, along the lines of the civilizing project outlined by the Republic, through the categories: Republicanism and scholastic model Souza (2012). Through the contributions on the concept of "comprehension and appropriation"; beyond the neologism "representância", for defining représentance in Ricoeur (1997/2010), in order to understand what was said and how it was narrated the experience of time, highlighting the significance of what has been ascribed by different subjects in different situations; centrality with the actions of individuals (Weber, 2001). Responding, thus the question-problem: How did the creation of the Group in Primary School Education in the State of Pará (1890-1910), from republicanism and of the school model, in its articulations with the educational, religious and political ideas? With emphasis on the analysis in the narratives expressed, in the primaries documentary sources: reports, regulations, decrees, books, official gazette, letters and newspapers; anchored in Schütze (2010), Ricoeur (2010), Creswell (2007) and Strauss and Corbin (2008). The results show that the Para was the third state to implement school groups, the institutionalization of them started by a municipality in in Alenquer in 1899, from the necessity of reorganization of primary education by 1899 Council Regulation and early twentieth century groups were created in the capital, in a scenario of modernization of the city of Belém, through urbanization, Belle Epoque and the height of the rubber boom.